GE_GERICHTE P/17332/2025 vom 29. August 2025 - GE Cour de justice (2025)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;QUALITÉ POUR AGIR ET RECOURIR;ESCROQUERIE;FAUX DANS LES CERTIFICATS;ASTUCE | CPP.310.al1.leta; CPP.382.al1; CP.179decies; CP.327; CP.146; CP.251